Effect of TCM-derived extracts on cataractdevelopment in the elderly: a pilot study - Woo, G. C.; Halpern, G. M.; Kwong, E. Y.M (Progress in Nutrition, 2010)
SummaryAs life expectancy increases worldwide, the incidence and prevalence of age-associated cataract do and impair the daily activities of millions. Correction is poor and surgery remains the most common solution, albeit out of reach for the vast majority of (poor) mankind. Reports on the efficacy of traditional Asian medicines (Chinese = TCM; Japanese = kampo) prompted us to evaluate a widely available/affordable TCM formula (GFDHW) in aged (≥ 60) subjects recruited from the Optometry Clinic of HKPU; 30 were enrolled and 22 completed the course. These subjects presented with mild cataract without any other significant health problem. After 90 days of GFDHW we did not observe any effect on the development and/or progression of cataract. However, a number of subjects reported improvement in areas of their “quality of life”. A pronged, placebo-controlled and comparative (e.g. Bawei Dihuang) study seems warranted.Effetto degli estratti derivati dalla Medicina Tradizionale Cinese sullo sviluppo della cataratta in anziani: uno studio pilotaRiassuntoCosì come l’aspettativa di vita sta aumentando in tutto il mondo, anche l’incidenza e la prevalenza della cataratta correlata all’età si diffonde e compromette l’attività quotidiana di milioni di persone. La correzione è scarsa e la chirurgia resta la soluzione più comune, anche se fuori dalla portata della stragrande maggioranza delle persone (classi più povere). I rapporti sull’efficacia delle Medicine Tradizionali Asiatiche (Cinese = TCM; Giapponese = kampo) hanno portato a valutare una formulazione della TCM (GFDHW), ampiamente disponibile/accessibile, in soggetti di età compresa o superiore ai 60 anni reclutati dalla Clinica Optometrica dell’Università Politecnica di Hong Kong; dei 30 arruolati per lo studio, 22 lo hanno completato. Questi soggetti presentavano una leggera cataratta senza altri significativi problemi di salute. Dopo 90 giorni di GFDHW non è stato osservato alcun effetto sullo sviluppo e/o sulla progressione della cataratta. Tuttavia, un certo numero di soggetti ha segnalato miglioramenti nella loro “qualità della vita”. Sembra pertanto giustificato uno studio placebo-controllato e comparativo (ad esempio Bawei Dihuang).